The Effect Of Ginger Candy (Zingiber Officinale Rosc.) on PGF2 A Levels in Adolescents with Primary Dysmenorrhea - Eka Tri Wulandari; Desi Kumalasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Primary dysmenorrhoea is a common complaint that is commonly experienced by women around the world, especially teenagers. One of the causes of primary dysmenorrhea is the hyperactivity of the myometrium which is modulated by the synthesis of prostaglandins, especially PGF2a. Some herbs are known to work as prostaglandin inhibitors, one of them is ginger. Giving ginger to adolescents who experience dysmenorrhea is expected to lower the levels of PGF2a so that dysmenorrhea pain can be reduced. Generally, ginger can be developed in a variety of food and beverage products such as jelly candy. The purpose of this study was to analyze the effect of ginger candy to decrease the level of PGF2a in adolescents with primary dysmenorrhoea. This research is analytic research that used a randomized pre-post group design experimental approach. The object of the research is 38 adolescents with primary dysmenorrhoea. the object is divided into two groups, 19 treatment groups and 19 control groups. the treatment group was given jelly candy containing 100 mg of ginger extract, while the control group was given jelly candy without ginger. The candy was given on the first day of menstruation until the second day of menstruation. The measurement of PGF2a level was on the second day of menstruation after the candy was given to the groups. The results showed that after the administration of candy, the last average levels of PGF2a in the treatment group decreased from 482,9 ng/ml to 370,5 ng, ml or down by 11%. Whereas in the control group, the PGF2a level 483,3 become 409,2. The difference in the percentage of decrease in the levels of PGF2a using the Mann-Whitney test showed a significant result (p=0,002). The conclusion of this research is ginger candy can reduce levels of PGF2a in adolescents with primary dysmenorrhoea Abstrak: Dismenorea primer merupakan keluhan umum yang biasa dialami oleh wanita di seluruh dunia terutama remaja. Salah satu penyebab terjadinya dismenorea primer adalah hiperaktivitas miometrium yang dimodulasi oleh sintesis prostaglandin, terutama PGF2a. Beberapa herbal diketahui dapat bekerja sebagai prostaglandin inhibitors, salah satunya jahe. Pemberian jahe pada remaja yang mengalami dismenorea diharapkan akan menurunkan kadar PGF2a sehingga nyeri dismenorea yang dirasakan akan berkurang. Secara umum jahe bisa dikembangkan dalam  berbagai produk makanan salah satunya permen. Tujuan penelitian ini adalah untuk menganalisa pengaruh pemberian permen jahe terhadap penurunan kadar PGF2a pada remaja yang mengalami dismenorea primer.Penelitian ini merupakan penelitian analitik dengan pendekatan eksperimental randomize pre post group design. Objek penelitian berjumlah 38 orang remaja yang mengalami dismenorea primer, objek dibagi menjadi 2 kelompok, yaitu 19 kelompok perlakuan dan 19 kelompok kontrol. Pada kelompok perlakuan diberikan permen jeli yang mengandung 100 mg ekstrak jahe, sedangkan pada kelompok kontrol diberikan permen jeli tanpa kandungan jahe. Pemberian permen dilakukan pada hari pertama menstruasi sampai hari ke dua menstruasi. Untuk pengukuran kadar PGF2a dilakukan pada hari ke 2 menstruasi setelah pemberian permen. Hasil penelitian menunjukan bahwa setelah pemberian permen, rerata kadar PGF2a pada kelompok perlakuan turun dari 482,9 ng/ml menjadi 370,5 ng/ml atau turun sebesar 11,5%, sedangkan pada kelompok kontrol dari 483,3 ng/ml menjadi 490,2 ng/ml. Perbedaan presentase penurunan kadar PGF2a pada kedua kelompok penelitian dengan menggunakan uji Mann Whitney menunjukan hasil yang bermakna (p=0,002).Simpulan dalam penelitian ini adalah permen jahe dapat menurunkan kadar PGF2a pada remaja yang mengalami dismenorea primer